The intramolecular 5-exo, 7-endo-dig transition metal-free cyclization sequence of (2-alkynylphenyl) benzyl ethers: synthesis of seven-membered fused benzo[b]furans. Issue 24 (26th October 2016) - Gai, Rafaela; do Carmo Pinheiro, Roberto; Neto, José S. S.; Iglesias, Bernardo A.; Acunha, Thiago V.; Back, Davi F.; Zeni, Gilson
Abstract : We present the results of the intramolecular transition metal-free cyclization of (2-alkynylphenyl) benzyl ethers promoted by sodium tert -butoxide. Abstract : Base-promoted cyclization of (2-alkynylphenyl) benzyl ethers was studied in detail. The effects of the solvent, base, temperature, reaction time and amount of base on the efficacy of the cyclization reaction were analyzed and a new base–solvent system ( tert -BuOK/DMSO) for effective cyclization of (2-alkynylphenyl) benzyl ethers was reported. The results showed that the cyclization reactions proceeded cleanly and smoothly under mild reaction conditions, employing tert -BuOK as a base, and DMSO as a solvent, at room temperature in a short reaction time (1 h). Under these conditions, a number of different substituted (2-alkynylphenyl) benzyl ethers were cyclized to the corresponding fused heterocycle cyclohepta[ b ]furans. This one-pot, two-step procedure occurred regioselectively giving only the cyclohepta[ b ]furans as the unique regioisomers via an initial intramolecular 5- exo -dig mode followed by an intramolecular 7- endo -dig mode. The cyclohepta[ b ]furan derivatives absorbed in the UV region (300–350 nm range) with molar absorptivity coefficient values attributed to spin and symmetry allowed π–π* electronic transitions. An emission located in the purple region (380–440 nm range), with a Stokes shift between 65–100 nm is probably associated with the charge transfer character of the excited state. The electrochemical analysis (CV) of the cyclohepta[ b ]furans showed an oxidation and reduction process, probably due to the presence of the selenium atom and π-anion radical species.